The Glycerol Phosphatase Gpp2: A Link to Osmotic Stress, Sulfur Assimilation and Virulence in Cryptococcus neoformans - Martho, Kevin Felipe; Brustolini, Otávio J. B.; Vasconcelos, Ana Tereza; Vallim, Marcelo A.; Pascon, Renata C. (Frontiers in Microbiology, 2019)
C. neoformans is an opportunist fungal pathogen that causes meningoencephalitis in immunocompromised patients. During infection, this basidiomycete yeast has to adapt to several adverse conditions, especially nutrient availability. The interruption on various amino acid biosynthetic pathways and on amino acid uptake causes reduced viability, inability to cope with various stresses, failure in virulence factors expression and avirulence in animal model of infection. The sulfur amino acid biosynthesis and uptake is an important feature for pathogen survival in vivo and in vitro. Our previous work demonstrates that C. neoformans Cys3 BZip transcription factor controls the gene expression in several steps of the sulfur assimilation and sulfur amino acid biosynthesis. Also, we have shown that Gpp2 phosphatase modulates Cys3 activity. In Saccharomyces cerevisiae Gpp2 is induced in response to hyper osmotic or oxidative stress and during diauxic shift. In this work, we will show that, in C. neoformans, Gpp2 is required to respond to stresses, mainly osmotic stress; also its transcription is induced during exposure to NaCl. Global transcriptional profile of gpp2 by RNAseq shows that CYS3 and other genes in the sulfur assimilation pathway are up regulated, which is consistent with our previous report, in which Gpp2 acts by avoiding Cys3 accumulation and nuclear localization. In addition, several transporters genes, especially amino acid permeases and oxidative stress genes are induced in the gpp2 strain; on the contrary, genes involved in glucose and tricarboxylic acid metabolism are down regulated. gpp2 strain fails to express virulence factors, as melanine, phospholipase, urease and has virulence attenuation in Galleria mellonella. Our data suggest that Gpp2 is an important factor for general pathogen adaptation to various stresses and also to the host, and perhaps it could be an interesting target for therapeutic use.